UiTMLaw Faculty ongoing food assistance program (alumni inspiration program with students: his excellency Datuk Wan Azmir Wan Majid & Seri Murni Welfare Foundation) - UiTM, Faculty of Law (Faculty of Law, 2023)
The Dean and people of UiTM Law would like to thank Yang Berbahagia Datuk Wan Azmi Wan Majid and the Seri Murni Welfare Foundation for the donation given to the students of the Faculty of Law, UiTM, during the Alumni and Student Inspiration Program. The program was also attended by the Chairman of the Seri Muni Charity Foundation, YB Dato' Tuan Muniandy, as well as members of the charity, namely Ms. Wan Azrina, Ms. Darshini, and Ms. Roselyn Bautista. YBhg Datuk Wan Azmir, in his speech, emphasized the importance of persevering in everything one undertakes and not giving up easily, no matter what challenges come. By sharing his experience, YBhg Datuk Wan Azmir reminded students who are confident of future sustenance thanks to the diligence shown while studying. May the contribution of YBhg Datuk Wan Azmir and Yayasan Kebajikan Seri Murni spark the right spirit among students to continue to study hard in order to taste success, and God will bestow him with all the goodness in the world.